Hubungan Penggunaan Media Sosial dan Peran Teman Sebaya Terhadap Perilaku Seksual Remaja di SMA Yayasan Perguruan Sinar Harapan Kec. Beringin Kab. Deli Serdang Tahun 2023 - Husniya Husniya; Petra Dian Sari Zega; Zulkarnain Batubara (Calory Journal Medical Laboratory Journal, 2023)
The use of social media and peer influence can provide a lot of information to teenagers, whether it is good information or has a negative impact on the teenager. To determine the relationship between the use of social media and peers on sexual behavior among teenagers at the Sinar Harapan College Foundation High School, Kec. Beringin Deli Serdang Regency in 2023. This research method is a quantitative method. The sample used Simple Random Sampling with the Slovin formula to obtain n= 62 respondents from each class. Primary data was obtained from distributing questionnaires. Data analysis was carried out using Univariate and Bivariate Analysis. Social media use among teenagers is categorized as moderate, 32.8% is categorized as low, and 60.4% is categorized as high. 21.6% of peer influence on adolescents is categorized as medium, 17.2% is categorized as low, and 61.2% is categorized as high. 65.7% of sexual behavior in adolescents is generally categorized as risky and 34.3% is categorized as not risky. There is a relationship between the use of social media and sexual behavior among teenagers at Sinar Husni High School which can be seen based on a p-value of 0.030 < 0.05. There is a relationship between social media and peers on sexual behavior among teenagers at Sinar Husni High School which can be seen based on a p-value of 0.034 < 0.05. There is a relationship between social media and peers on sexual behavior among teenagers at Sinar Harapan College Foundation High School.